Western Europe as a Model for Polish Defenders of Animal Welfare prior to 1939 - Kasprzycki, Remigiusz (Kwartalnik Historyczny, 2023)
This article looks at how Western Europe served as a model for Polish animal advocates before 1939. France and Great Britain inspired the greatest respect among Polish animal defenders. Polish animal lovers, fascinated by the French and English treatment of animals, discovered the effectiveness of grassroots initiatives, rather than legal resolutions and acts, for the welfare of animals. This article attempts to explain why the endeavour to copy the treatment of animals by wealthy Germans, French, and above all English and introduce it to economically poor Poland proved to be utopian.